Rapid and Sensitive Method for Detection of Y402, H402, I62, and V62 Variants of Complement Factor H in Human Plasma Samples Using Mass Spectrometry - Kelly, Una (2008)
PURPOSE: Variations in the complement factor H (CFH) gene are tightly associated with age-related macular degeneration (AMD) across diverse populations. Of the many nonsynonymous coding variants in CFH, two are most strongly associated with increased risk of AMD: isoleucine 62 to valine (I62V) and tyrosine 402 to histidine (Y402H). Detection of these variations in a patient’s blood is important for a risk assessment of AMD and disease prognosis. However, traditional methods of genetic analysis cannot be used for measuring CFH allotypes in some sources of human plasma and other biological fluids not containing DNA. The purpose was to develop a protein-based method of detecting CFH allotypes. METHODS: A combination of a single-step affinity enrichment of CFH, gel separation, and mass spectrometry identification of the CFH peptides spanning amino acids at positions 62 and 402 was used to identify individual CFH allotypes. RESULTS: The CFH isoforms V62, I62, H402, and Y402 were reliably detected based on identification of tryptic peptides with masses of 1148.59 Da, 1162.60 Da, 2031.88 Da, and 2057.88 Da, respectively, using MALDI-TOF-TOF. The presence or absence pattern of these peptides in mass spectra of different CFH samples robustly correlated with all nine genotypes of CFH, as a result of variations at positions 62 and 402. CONCLUSIONS: A rapid and sensitive method has been developed for detection of V62, I62, H402, and Y402 variants of CFH in human plasma samples using mass spectrometry. This method can be used in clinical laboratories equipped with a basic inexpensive mass spectrometer capable of performing peptide fingerprinting.